Filozofia edukacji Edmunda Bojanowskiego w perspektywie XIX-wiecznej filozofii polskiej oraz filozofii klasycznej - Krasnodębski, Mikołaj (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Edmund Bojanowski – the founder of Orphanages and The Congregation of Sisters Servants of the Immaculate Conception of the Blessed Virgin Mary didn’t leave any philosophical works behind. In spite of this as a teacher and community worker he created his own philosophy of act based on the classical and neoscholastic philosophy. It was very original and inspiring in the context of the nineteenth-century philosophy and is still relevant. In this paper the philosophical fundaments on which Edmund Bojanowski built his concept of education have been shown.